Hungarian Low Rank Coal Gasification and Single Line Multi-Stage Gasification: Short Review - Mai, Duc Thuan; Kállay, András Arnold (Hungarian materials and chemical sciences and engineering (Online), 2023)
Presently, the thermochemical process is widely used in the utilisation of fossil fuels. In which, gasification processes are the most attractive solutions for the cleaner utilisation of coal. One of the main challenges is the development of the reactor considering a better conversion efficiency. In this paper, the background research shows that there is a field of research with a gap within the gasification of low rank coals, especially regarding the fine-tuning of the synthesis gas composition within the process. There are several research focusing on multistage gasifiers, however, these approaches mainly focused on the multi-stage gasification of biomass fuel to enhance the quality of synthesis gas, especially in the reduction of tar content to use in combustion process as internal combustion engine or combined heat and power plant. In addition, using air as reactant showed the poor result in the ratio of H2/CO for further direct application in the chemical process.